Generation Y: do millennials need a partner to be happy? - Scheling, Louisa; Richter, David (Journal of adolescence, 2021)
Introduction - Empirical evidence on Ronald Inglehart's theory of value change shows that subsequent generations show a decline in values of physical and economic security (materialism) in favor of an increase in values of self-expression and autonomy (postmaterialism). - Methods - We investigate in a pre-registered study whether Inglehart's theory also applies to partnership, such that millennials think less that they need a partner to be happy. We used data from the German Socio-Economic Panel (SOEP) study on 4540 17-year-olds from 16 birth cohorts. - Results - Results show that adolescents’ estimated importance of a romantic partner for personal happiness decreases on average with each subsequent birth cohort. Further significant predictors were socialization and relationship status of the parents, birth year of the father, as well as education and sex of the adolescent. Socioeconomic status and education level of the parents and birth year of the mother were not significant. - Conclusions - Findings provide initial evidence that as society becomes more individualized, even personal happiness is increasingly seen as independent of significant others. Ronald Inglehart's theory of value change, however, seems to have only limited applicability as an explanatory model for this development.